Design, Synthesis, and Activity Assays of Cyclin-Dependent Kinase 1 Inhibitors With Flavone Scaffolds - Fu, Lanlan; Mou, Jiajia; Deng, Yanru; Ren, Xiaoliang; Qiu, Shuang (Frontiers in Chemistry, 2022)
Cyclin-dependent kinases 1 (CDK1) plays an indispensable role in the whole cell cycle. It has become a new target for cancers therapy. According to the binding mode of a pan-CDK inhibitor, flavopiridol with CDK1 and our previous work, a new series of flavone derivatives were discovered. Among them, compound 2a showed the best CDK1 inhibitory and anti-proliferative potencies in the in vitro activity investigation. The IC50 of 2a against CDK1 was 36.42±1.12 μM vs. 11.49 μM±0.56 of flavopiridol. In the anti-proliferation activity assays, 2a exhibited better activity towards RAW264.7 than MCF-7 cells. The results indicated that flavone derivatives, besides inhibiting the growth of tumor cells, can also antagonize inflammatory response. Molecular docking results showed that conformation of 2a can form hydrogen bonds and various hydrophobic interactions with the key amino acid residues of CDK1. It can be used as a promising lead compound for CDK1 inhibitor development.